Shönlein-Henoch Purpura in the Course of Chronic Primary Inmmune Thrombocytopenia. Presentation of a Case - Lucía Díaz Morejón; Belkis Lázara Rodríguez Jorge; Dumeivy García Sánchez (Revista Finlay)
Shönlein-Henoch purpura is a common vasculatis in childhood, characterized by a non-trombocytopenic palpable purpura and systemic manifestations, accompanied by abdominal pain, gastro-intestinal bleeding, glomerulonephritis, arthritis and arthralgias. It is the most common of diseases due to disturbances in the vascular component in children. It is related to triggering pathologies as infections and insect bites. A case of a 4 year old boy is presented who presented allergic episodes of rhinitis and urticaria. He had been diagnosed with an chronic primary inmmune thrombocytopenia. In spite of the different treatment approaches, the patient had a severe thrombocytopenia, associated to purpura and macolu-papular lesions and uticaria. Lab tests, with the exception of platelet count, were within the normal limits. The progress was satisfactory in a three week period.